Integrating Artificial Intelligence in Teaching Arabic as a Foreign Language (TAFL) at MTsN 1 Surabaya - Abdullah Hussein; Ni Wayan (Institut Studi Islam Muhammadiyah Pacitan, 2026)
The rapid evolution of educational technology has positioned Artificial Intelligence (AI) as a transformative force in language education. AI can enhance instruction, personalize learning, and support pedagogical innovation for learners of Arabic as a Foreign Language (TAFL). This paper examines the integration of AI in TAFL pedagogy with specific reference to its potential application at MTsN 1 Surabaya, an Indonesian Islamic junior high school. Although limited direct research exists on MTsN 1 Surabaya’s implementation of AI, broader studies in Arabic education and AI provide a theoretical basis for integrating intelligent systems into TAFL instruction. Drawing on recent research on AI’s role in Arabic learning such as adaptive systems, chatbots, automated feedback tools, and speech recognition this study outlines potential benefits, midstream challenges, and strategies for AI-enhanced language instruction. Such integration offers personalized learning, real-time feedback, improved motivation, and enhanced instructional delivery. However, success depends on teacher preparedness, infrastructure, and curriculum alignment with AI capabilities. This paper contributes to the understanding of how TAFL at MTsN 1 Surabaya can be reimagined through AI, with implications for pedagogy, policy, and future research.